2002
DOI: 10.1159/000071588
|View full text |Cite
|
Sign up to set email alerts
|

Early origins of the X and Y chromosomes: Lessons from tilapia

Abstract: Differentiated sex chromosome pairs in diverse species display certain common characteristics, normally comprising one largely heterochromatic genetically inactive chromosome and one euchromatic genetically active chromosome (e.g. the mammalian Y and X respectively). It is widely accepted that dimorphic sex chromosomes evolved from homologous pairs of autosomes. Although the exact mechanisms through which the pair diverged are not fully understood, an initial suppression of recombination in the sex-determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 31 publications
(36 reference statements)
1
44
0
6
Order By: Relevance
“…In salmonids (male heterogamety), comparative mapping of sexlinked microsatellite markers has already shown that Arctic charr, brown trout, Atlantic salmon and rainbow trout have evolved different sex chromosomes (Woram et al, 2003). Sex-linked markers have been found in the Nile tilapia Oreochromis niloticus (XX/XY) and the blue tilapia O. aureus (ZW/ZZ) (Lee et al, 2004), and the putative sex chromosomes have been identified by synaptonemal complex analysis (for a review, Griffin et al, 2002). In the threespine stickleback, sequencing of X-and Y-specific bacterial artificial chromosome clones from the sex determination region revealed many sequence differences between X and neo-Y chromosomes .…”
Section: Transposable Elements and Speciationmentioning
confidence: 99%
“…In salmonids (male heterogamety), comparative mapping of sexlinked microsatellite markers has already shown that Arctic charr, brown trout, Atlantic salmon and rainbow trout have evolved different sex chromosomes (Woram et al, 2003). Sex-linked markers have been found in the Nile tilapia Oreochromis niloticus (XX/XY) and the blue tilapia O. aureus (ZW/ZZ) (Lee et al, 2004), and the putative sex chromosomes have been identified by synaptonemal complex analysis (for a review, Griffin et al, 2002). In the threespine stickleback, sequencing of X-and Y-specific bacterial artificial chromosome clones from the sex determination region revealed many sequence differences between X and neo-Y chromosomes .…”
Section: Transposable Elements and Speciationmentioning
confidence: 99%
“…To prevent the production of infertile individuals, recombination of these loci becomes restricted [3,4]. This crucial step is intensively debated and two mechanisms of action have been proposed: (i) structural changes by translocation or inversion (reviewed in [5]); or (ii) chromatin status changes involving heterochromatization of the heterosexual chromosome [4,6-9]. Heterochromatization of the sex-determining region has been shown in species with primitive or nascent sex chromosomes, such as in papaya or tilapia (reviewed in [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the mechanism of recombination repression between S. mansoni sex chromosomes is not clear. As outlined above, either inversion events or heterochromatization [7,9,23] have been proposed for other species. The specific objectives of the present study were to determine what the sex-specific DNA sequences of S. mansoni are, and how heterochromatization of the W chromosome might be initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Birds are probably the best-cited example, but Lepidoptera (butterflies and moths), snakes, and some fish and reptiles also have ZW systems. In some groups of animals, both ZW and XY systems are reported in the same groups (Organ and Janes 2008;Ross et al 2009) even at the level of the same genera (Campos-Ramos et al 2001;Griffin et al 2000;Harvey et al 2002;Takehana et al 2007) or species (Ogata et al 2007). While there are a number of examples of fish (Kondo et al 2004;Peichel et al 2004), insects (Bachtrog and Charlesworth 2002;Benatti et al 2010), and plants (Liu et al 2004;Filatov 2005) with novel sex chromosome systems close to the beginning of the degenerative process, neo-sex chromosomes have been identified in very few mammalian, avian or insect species (Zhou et al 2008;Pala et al 2011;Carvalho and Clark 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While genetic sex determination is by no means the only way of promoting dioecy (phenotypically distinct males and females) it is an effective one, and sex chromosome differentiation often follows the evolution of a sexdetermining locus such as SRY. A cycle of events that near-obliterates the Y chromosome ensues; this includes reduction in recombination around the sexdetermining region that could have initially been a consequence of a de novo stochastic expansion of heterochromatin (Griffin et al 2000). In any event, the presence of a sex-determining locus drives a series of events-recombination reduction-loss of euchromatin-expansion of heterochromatin-loss of recombination and so on; events that are bad news for the Y (Graves 1995).…”
Section: Introductionmentioning
confidence: 99%